Non-metric variations in individuals who died during the perinatal period in past populations: recording protocol and comparative data - Caroline Partiot; Dominique Castex; Valérie Delattre; Bruno Maureille; Mark Guillon (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Non-metric variations, also referred to as "epigenetic variations" or asymptomatic bone variants, are bone or dental phenotypic variants of unknown origin, with no known pathological etiology. They are classically identified during osteological analysis to develop an individual profile, analyse biological affinities between individuals and outline possible genetic relatedness clusters in burial spaces. However, although numerous studies have focused on their occurrence in adult archaeological samples, data on their development, expression and frequency in skeletally immature individuals are still scarce. The aim of this study was therefore to document the expression and frequencies of a selection of non-metric variations in an archaeological sample of 116 individuals who died during the perinatal period, in order to outline a diachronic reference database for comparative analysis. The individuals analysed are from an ancient Sudanese necropolis and two medieval/modern cemeteries and churches in the Paris Basin. Altogether, the occurrence of 22 selected variants were scored directly from the examination of the bones. No significant population-based difference was found between the Nubian and the Western European samples. Frequencies in the perinatal sample were compared with those of samples including juvenile and adult individuals from other chrono-geographical contexts.